Résister aux projets d’aménagement, politiser les territoires - Léa Sébastien; Julien Milanesi; Jérôme Pelenc (VertigO)
In this article we formulate the hypothesis that resistance to development projects could be considered as an opportunity for the (re) politicization of territories. By looking at three cases of place-based struggles against infrastructures (a landfill, a highway and a prison), we analyze the evolution of these resistance movements over time through the concept of enlightening resistance. This concept allows us to see the emergence of new social networks, specific knowledge and attachments to the threatened places. We argue that the development and combination of these three types of "capital" (social, patrimonial, knowledge) allow the emergence of a political capital. On the contrary to the NIMBY (not in my back yard) label, we show thanks to the concept of enlightening resistance, that these place-based struggles participate in the emergence of a decentralized social movement promoting new democratic and socio-ecological values.